Baseball Joe, Home Run King; or, The Greatest Pitcher and Batter on Record - Chadwick, Lester, 1873-1962 (Salt Lake City, UT : Project Gutenberg, 2013)
"Baseball Joe, Home Run King; or, The Greatest Pitcher and Batter on Record" by Lester Chadwick is a sports novel written in the early 20th century. The story revolves around the exploits of Joe Matson, celebrated as "Baseball Joe," who is not only a phenomenal pitcher but also an impressive batter, continuously defying common perceptions about pitchers' hitting abilities. With the setup of baseball training and competition, the narrative follows Joe's journey as he prepares for a new season, addresses personal relationships, and confronts rivals both on and off the field. At the start of the novel, readers are introduced to Joe and his friend Jim Barclay during a batting practice session where Joe impressively hits a home run, showcasing his dual talents. Their lively camaraderie is evident as they prepare to return home, but there's an underlying tension introduced when Jim suspects that a past adversary, Braxton, might be lurking nearby, potentially plotting revenge against Joe. As the narrative unfolds, the plot hints at danger and rivalry amidst the backdrop of baseball drama. The opening establishes a dynamic tension between the thrill of the sport and the personal stakes Joe faces, inviting readers into a world where athletic prowess and personal honor collide. (This is an automatically generated summary.)
Release date is 2013-10-12
E-text prepared by Donald Cummings and the Online Distributed Proofreading Team
Keywords: Conduct of life -- Juvenile fiction; Young men -- Conduct of life -- Juvenile fiction; Kidnapping -- Juvenile fiction; Diligence -- Juvenile fiction; Success -- Juvenile fiction; Fortune -- Juvenile fiction; Baseball stories; Baseball players -- Juvenile fiction; New York Giants (Baseball team) -- Juvenile fiction